Geologi, Karakteristik Alterasi Hidrotermal dan Mineralisasi Bijih pada Pit Purnama Martabe, Kabupaten Tapanuli Selatan, Provinsi Sumatera Utara - Theresia Fernandha Samuels; Arifudin Idrus (PROMINE, 2021)
High demands of metal such as gold, silver, and copper, also their limited occurances causing an understanding of geological conditions, alteration and ore mineralization characteristics are needed for a sustainable exploration. This study aims to elucidate geological conditions, characteristics and the distribution of alteration zones and ores mineralization in Purnama Martabe Pit based on geological mapping, drill cores logging and sampling. Selected samples were analysed by XRF (X-Ray Fluorescenes), ASD (Analytical Spectral Devices), petrography, and mineragraphy analysis. Lithological units at the study area consist of andesite lava unit, diorite intrusion dome and polymictic phreatomagmatic breccia units. Based on ASD analysis, alteration zones in the study area are vuggy-massive silica, silica+dickite±alunite, illite+smectite, and smectite+chlorite. Based on mineragraphy and XRF, the mineralization occurred at the study area is composed of pyrite, enargite, hematite, goethite, and jarosite. Zonation and distribution of alteration and mineralization is predominantly controlled by the north east – south west structure in the form of quartz veins, north west – south east structure, and various porosities of the lithological units.